Gaya Kepemimpinan Mudir Dalam Mencetak Da’i Di Pondok Pesantren Raudhatul Qur’an Desa Payaraman Kabupaten Ogan Ilir - Aliya Saputri; Candra Darmawan (Social Science and Contemporary Issues Journal, 2024)
This thesis is entitled "Mudir Leadership Style in producing Da'i at the Raudhatul Qur'an Islamic Boarding School, Payaraman Village, Ogan Ilir Regency". The background of this research is the lack of mudir leadership in producing preachers at the Raudhatul Qur'an Islamic Boarding School. The purpose of this research is to determine the leadership style in producing preachers at the Raudhtaul Qur'an Islamic boarding school and to determine the supporting and inhibiting factors for a student to become a preacher at the Raudhtaul Qur'an Islamic boarding school. The approach used in this research is a qualitative method with a descriptive approach. The data collection techniques include observation, interviews and documentation techniques using primary and secondary data. Meanwhile, the data analysis technique used is interactive analysis, namely data reduction, data presentation and drawing conclusions. The theory used in this research is the Evans-Haous path-goal theory related to leadership style and the theory of Faizah and Lula Machsin Effendi related to the nature of a preacher. Based on the results of this research, it shows that the mudir leadership style has a significant influence on producing preachers. A leadership style that is inclusive, motivating and provides good examples tends to produce quality preachers who are able to become role models for society, and the inhibiting and supporting factors for santri to become preachers, the inhibiting factors are lack of motivation and lack of Islamic boarding school religious education facilities. And the supporting factors motivate students internally, adequate educational facilities for students. Thus, this research examines the importance of the mudir's role in producing competent and integrated preachers at the Raudhatul Qur'an Payaraman Islamic Boarding School, so that they can contribute positively to building society and the people.Keywords: Leadership style, Printing Da'i.